PENGARUH MOTIVASI TERHADAP KOMPETENSI DAN DAMPAKNYA PADA KINERJA KARYAWAN PUSKESMAS DI SURABAYA - Wahdini, Ratnaika; Wardoyo, Dewie Tri Wijayati; Witjaksono, Andre Dwijanto (JURNAL ILMIAH EDUNOMIKA, 2024)
This study, titled "The Influence of Motivation on Employee Performance Through Employee Competence at Puskesmas in Surabaya," aims to analyze the effect of work motivation on employee performance while considering the role of employee competence as a mediating variable. The research employs Structural Equation Modeling (SEM) to examine the causal relationships between motivation, competence, and employee performance across five Puskesmas in Surabaya. Data were collected through a survey involving 163 employees, utilizing a questionnaire consisting of 54 questions related to motivation, competence, and performance. The analysis results indicate that work motivation has a positive but statistically insignificant direct effect on employee performance, with a path coefficient of 0.162 (p < 0.05). This suggests that while work motivation may have a beneficial impact, other factors might also play a significant role in determining employee performance. Furthermore, work motivation was found to have a significant positive influence on employee competence, with a path coefficient of 0.571 (p < 0.05). In turn, employee competence significantly positively affects employee performance, with a path coefficient of 0.560 (p < 0.05). Additionally, work motivation indirectly influences employee performance through competence, with a path coefficient of 0.320 (p < 0.05). This study concludes that enhancing employee motivation and competence will positively impact employee performance at Puskesmas. The implications of these findings are expected to provide recommendations for Puskesmas management in designing effective employee development strategies and contribute to the literature on human resource management in the healthcare sector.